Trametes versicolor laccase production using agricultural wastes: a comparative study in Erlenmeyer flasks, bioreactor and tray - Pinheiro, Vanessa Elisa (2020)
Electronic supplementary material The online version of this article (https://doi.org/10.1007/s00449-019-02245-z) contains supplementary material, which is available to authorized users.